Association of ABO Neo-maternal Incompatibility and Neonatal Jaundice in Nguru, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:ABO blood group antigens are inherited and specific to an individual. In pregnancy, active immunisation occurs when the foetus is of a different ABO blood group from the mother and may result in neonatal jaundice (NNJ). Therefore, monitoring and evaluation of mothers at booking and throughout pregnancy and the postpartum period is important in management.Aim:The aim of this study is to determine the prevalence of neo-maternal ABO blood group incompatibility and to assess any relationship with NNJ among mother-neonate pairs in Nguru, Northeast Nigeria.Subjects and Methods:This was a cross-sectional descriptive study of 200 pregnant women at Federal Medical Centre, Nguru, Yobe State, Nigeria in 2015. ABO blood group antigens of both mothers and neonates were determined while direct Coomb’s test (DCT), full blood counts, reticulocyte counts and bilirubin assays were determined for neonates of ABO-incompatible neo-maternal pairs. Data were analysed using SPSS Version 20, and aP≤ 0.05 was considered as statistically significant.Results:The mean age of the mothers was 26.4 ± 6.2 years. Blood group O had the highest frequencies among mothers and neonates 58% and 57.5%, respectively. Although 28% of the mother-neonate pairs were ABO blood group incompatible, only 12.5% of the incompatible neonates had a positive cord blood DCT, and only 6% of the neonates developed jaundice. There was a strong and positive association between ABO neo-maternal blood group incompatibility and NNJP= 0.007 (Fishers’ exact test), odds ratio = 8.52, 95% confidence interval; 1.665, 43.591.Conclusion:ABO neo-maternal incompatibility is common, and it has a strong positive association with NNJ. There is a need for routine neonatal ABO screening, especially where jaundice exists.